Shortfall aversion. (4th March 2020) - Guasoni, Paolo; Huberman, Gur; Ren, Dan
Abstract: Shortfall aversion reflects the higher utility loss of spending cuts from a reference than the utility gain from similar spending increases. Inspired by Prospect Theory's loss aversion and the peak‐end rule, this paper posits a model of utility from spending scaled by past peak spending. In contrast to traditional models, which call for spending rates proportional to wealth, the optimal policy in this model implies a constant spending rate equal to the historical peak when wealth is relatively large. The spending rate increases when wealth reaches a model‐determined multiple of peak spending. In 1926–2015, shortfall‐averse spending is smooth and typically increasing.